Novel device-based interventional strategies for advanced heart failure - Toth, Gabor G.; Vanderheyden, Marc; Bartunek, Jozef (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2016)
While heart failure is one of the leading causes of mortality and morbidity, our tools to provide ultimate treatment solutions are still limited. Recent developments in new devices are designed to fill this therapeutic gap. The scope of this review is to focus on two particular targets, namely (1) left ventricular geometric restoration and (2) atrial depressurization. (1) Reduction of the wall stress by shrinking the ventricular cavity has been traditionally attempted surgically. Recently, the Parachute device (CardioKinetix Inc., Menlo Park, CA, USA) has been introduced to restore ventricular geometry and cardiac mechanics. The intervention aims to partition distal dysfunctional segments that are non-contributory to the ventricular mechanics and forward cardiac output. (2) Diastolic heart failure is characterized by abnormal relaxation and chamber stiffness. The main therapeutic goal achieved should be the reduction of afterload and diastolic pressure load. Recently, new catheter-based approaches were proposed to reduce left atrial pressure and ventricular decompression: the InterAtrial Shunt Device (IASDTM) (Corvia Medical Inc., Tewksbury, MA, USA) and the V-Wave Shunt (V-Wave Ltd, Or Akiva, Israel). Both are designed to create a controlled atrial septal defect in symptomatic patients with heart failure. While the assist devices are aimed at end-stage heart failure, emerging device-based percutaneous or minimal invasive techniques comprise a wide spectrum of innovative concepts that target ventricular remodeling, cardiac contractility or neuro-humoral modulation. The clinical adoption is in the early stages of the initial feasibility and safety studies, and clinical evidence needs to be gathered in appropriately designed clinical trials.